Challenges of Islamic Religious Higher Education in Indonesia: Qualitative Analysis Using NVivo Software - Septa Riadi; Ahiruddin Ahiruddin; Kuswarak Kuswarak; Husna Purnama (CV. Tripe Konsultan, 2021)
This study aims to analyze and examine the main issues in any news on the internet related to the challenges of Islamic Religious Higher Education. Online News is obtained using the Google Indonesia search engine using the keyword